Image-guided Control of Transgene Expression Based on Local Hyperthermia - E. Guilhon; B. Quesson; F. Moraud-Gaudry; H. de Verneuil; P. Canioni; R. Salomir; P. Voisin; C. T. W. Moonen (Molecular Imaging)
Spatial and temporal control of transgene expression is one of the major prerequisites of efficient gene therapy. Recently, a noninvasive, physical approach has been presented based on local heat in combination with a heat-sensitive promoter. This strategy requires tight temperature control in vivo. Here, we use MRI-guided focused ultrasound (MRI-FUS) with real-time feedback control on a whole-body clinical MRI system for a completely automatic execution of a predefined temperature-time trajectory in the focal point. Feasibility studies on expression control were carried out on subcutaneously implanted rat tumors. A stable modified C6 glioma cell line was used carrying a fused gene coding for thymidine kinase (TK) and green fluorescent protein (GFP) under control of the human heat-shock protein 70 (HSP70) promoter. In vitro studies showed strong induction of the TK-GFP gene expression upon heat shock under various conditions and localization of the protein product in the nucleus. In vivo tumors were subjected to a 3-min temperature elevation using MRI-FUS with a constant temperature, and were analysed 24 hr after the heat shock with respect to GFP fluorescence. Preliminary results showed strong local induction in regions heated above 40°C, and a good correspondence between temperature maps at the end of the heating period and elevated expression of TK-GFP.